Hardfacing studies of Ni alloys: a critical review - S. Balaguru; M. Gupta (Journal of Materials Research and Technology, 2021)
Hardfacing is done to increase the service life of structural components. Hardfacing is widely done in nuclear and petrochemical industries, mining and sugar refineries. Hardfacing is done on farming equipment to extend their service life as they are prone to impact, abrasion and corrosion. Generally, Ni-base, Co-base and Fe-base alloys are used for hardfacings. Among them, Ni-base alloys are preferred to Co-base and Fe-base alloys as these alloys can retain its hardness even at the elevated temperatures. Colmonoy alloys are predominantly used in nuclear reactor as the dose rate of these alloys is 1/265th that of Co-base alloys. Plasma Transferred Arc (PTA), Gas Tungsten Arc (GTA) and Laser are the major hardfacing processes. The hardfacing process governs the four major aspects of the coating, viz. microstructure, substrate dilution, wear and mechanical properties. This paper provides an in-depth understanding of various research works carried out on Ni alloy hardfacings by different processes on different substrates in those four domains. The outcome of this paper would be beneficial to present and future researchers on Ni alloy hardfacings and also to many hardfacing industries.